What's the Impediment?: Structural and Legal Constraints to Shared Governance in the Community College - Levin, John S. (Canadian Journal of Higher Education, 2000)
This research examines the legal foundations and bases for shared or co-governance in the community college through an examination of government legislation and institutional collective agreements between colleges and faculty in two countries, Canada and the U.S. This multi-case investigation identifies impediments to shared governance, and concludes that except in one legal jurisdiction, shared governance is either impeded legally or not supported by government legislation.